Desain Kurikulum Pendidikan Islam: Sebuah Kajian Literatur - Rohman, Syaifur; Bima Fandi Asy’arie; Bunayar, Bunayar (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
Abstract: In facing the challenges of contemporary times, relevant curriculum design in Islamic education is very important. Where students can gain a deeper understanding of Islamic teachings that are appropriate to the context of the times through a proper curriculum. The established curriculum can help students deal with various problems, technological developments, morals, spirituality, etc. Therefore, curriculum design in accordance with Islamic education is very important to ensure that education provides values ​​that are beneficial for student development and meet the demands of the times. This research is to describe (1) basic curriculum concepts, (2) the basis for curriculum design, and (3) components of curriculum design in Islamic education. This research uses a type of library research approach. Literature is obtained from various sources, books, scientific journals, and similar publications using online databases such as “Google Scholar,” and “ScienceDirect.” As for the discussion in this article, First, the basic concepts of the curriculum include: “definition, form and role, steps and principles, orientation and function.” Second, the curriculum design basis, which includes: “philosophical, psychological, sociological, scientific and technological (IPTEK) foundations,” Third, components of curriculum design in Islamic education, which include: “educational objectives, teaching materials or learning material content, learning strategies, learning evaluation.”